Host galaxy magnitude of OJ 287 from its colours at minimum light. Issue 2 (2nd June 2022) - Valtonen, Mauri J; Dey, Lankeswar; Zola, S; Ciprini, S; Kidger, M; Pursimo, T; Gopakumar, A; Matsumoto, K; Sadakane, K; Caton, D B; Nilsson, K; Komossa, S; et al.
ABSTRACT: OJ 287 is a BL Lacertae type quasar in which the active galactic nucleus (AGN) outshines the host galaxy by an order of magnitude. The only exception to this may be at minimum light when the AGN activity is so low that the host galaxy may make quite a considerable contribution to the photometric intensity of the source. Such a dip or a fade in the intensity of OJ 287 occurred in 2017 November, when its brightness was about 1.75 mag lower than the recent mean level. We compare the observations of this fade with similar fades in OJ 287 observed earlier in 1989, 1999, and 2010. It appears that there is a relatively strong reddening of the B − V colours of OJ 287 when its V -band brightness drops below magnitude 17. Similar changes are also seen in V − R, V − I, and R − I colours during these deep fades. These data support the conclusion that the total magnitude of the host galaxy is V = 18.0 ± 0.3, corresponding to MK = −26.5 ± 0.3 in the K -band. This is in agreement with the results, obtained using the integrated surface brightness method, from recent surface photometry of the host. These results should encourage us to use the colour separation method also in other host galaxies with strongly variable AGN. In the case of OJ 287, both the host galaxy and its central black hole are among the biggest known, and its position in the black hole mass–galaxy mass diagram lies close to the mean correlation.